La cultura organizacional, su importancia en el desarrollo de las empresas - Guerrero Bejarano, María Auxiliadora (2017)
In the current market, in which to keep, develop and move from one stage of life to another, within the business life cycle, is increasingly complex, we analyze the different reasons why some organizations obtain better results what others; for some decades academics and practicioner have turned their attention to the human resource as an important factor for the achievement of the goals set by the companies. This theoretical analysis seeks to understand organizational culture as one of the factors that could insinuate in the development of companies.